Model Implementasi Zakat Sebagai Instrumen Jaminan Sosial (Kajian Pada Baitulmal Majlis Agama Islam Wilayah Persekutuan, Malaysia) - Aidil Alfin (Sharia and Law Faculty, 2017)
This article discusses the Baitulmal of Majlis Islam Wilayah Persekutuan (MAIWP) Malaysia and the implementation of zakat as an instrument of social security especially in Federal Territory of Kuala Lumpur. Considering the experiences and achievements of the institution in the past, this article discusses the possibility of formulating zakat as an instrument of social security for the whole Malaysia.